The solace of bay leaves - Budewitz, Leslie (Budewitz, Leslie. Spice shop mystery, 2020)
"Pepper Reece never expected to find solace in bay leaves. But when her life fell apart at forty and she bought the venerable-but-rundown Spice Shop in Seattle's Pike Place Market, her days took a tasty turn. Now she's savoring the prospect of a flavorful fall and a busy holiday cooking season, until danger bubbles to the surface . . .Between managing her shop, worrying about her staff, and navigating a delicious new relationship, Pepper's firing on all burners. But when her childhood friend Maddie is shot and gravely wounded, the incident is quickly tied to an unsolved murder that left another close friend a widow.Convinced that the secret to both crimes lies in the history of a once-beloved building, Pepper uses her local-girl contacts and her talent for asking questions to unearth startling links between the past and present - links that suggest her childhood friend may not have been the Golden Girl she appeared to be. Pepper is forced to face her own regrets and unsavory emotions, if she wants to save Maddie's life - and her own."--Publisher.